Supply chain network strategy for microfluidic-based clinical diagnostic device - Ng, Sing Hng (2014)
Although microfluidic technology is at its infancy stage, it offers many advantages for disease screening. In this thesis, our focus is to develop the supply chain strategies for serving the elusive pandemic demand in Singapore. To make the supply chain more robust, a few opportunities for delayed differentiation are identified. Next, demand-capacity evaluations for pandemic disease screening device were performed which suggests that the pandemic demand in Singapore is too low to warrant the establishment of a dedicated production facility. If a production facility is to be built, a possible business model could be to produce normal blood testing kits and reserved some capacity to satisfy the pandemic demand. Several production options are then discussed and that the production facility is advised to choose the option which can bring the highest expected profit.